Magnetic Patterning: Local Photothermal Control of Phase Transitions for On‐Demand Room‐Temperature Rewritable Magnetic Patterning (Adv. Mater. 22/2020). Issue 22 (2nd June 2020) - Mei, Antonio B.; Gray, Isaiah; Tang, Yongjian; Schubert, Jürgen; Werder, Don; Bartell, Jason; Ralph, Daniel C.; Fuchs, Gregory D.; Schlom, Darrell G.
Abstract : Patterned magnetic nanostructures are foundational to magnetic memory and logic devices. In article number 2001080, Antonio B. Mei, Gregory D. Fuchs, and co‐workers design a platform for reconfigurable magnetic nanostructures in FeRh by tuning the transition temperature from antiferromagnetic to ferromagnetic such that both phases are stable at room temperature. Focused laser heating is used to write ferromagnetic patterns of arbitrary shape at ultrafast speeds, which can be erased by cooling below room temperature.